Embed theory of planned behavior in predicting external financing of woman’s entrepreneur behavior - Rauly Sijabat; Noni Setyorini; Fatkhul Amin; Prianka Ratri Nastiti (International Enterprise Integration Association, 2026)
Empirical gaps regarding high credit interest rates, male dominance of asset ownership, the tendency to use own capital to start small businesses, gender discrimination, and a higher risk of credit rejection are reasons why female entrepreneurs are reluctant to apply for business loans. Individual investment behavior is influenced by gender differences. Previous research due to indications of behavioral differences between female and male entrepreneurs in making business debt decisions. Also found that individual debt or investment behavior is largely determined by personal attributes, one of which is gender. Based empirical gap and research gap perspective, the implementation of the Theory of Planned Behavior (THB) in entrepreneurship studies, particularly on business debt behavior with female entrepreneurs as the subject, is still very limited, if not non-existent. Furthermore, the factors tested have not specifically mapped research variables to factors such as attitude, subjective norms, and perceived behavioral control. So, it is necessary to develop a fundamental, theory-based model using the TPB approach that can organize predictor variables and comprehensively and systematically predict and explain business debt behavior among female entrepreneurs. The empirical model was tested using empirical data obtained from interviews with female entrepreneurs who had business debt for the purposes of establishing or expanding their businesses. The model testing and the influence between variables were then analyzed using a Structural Equation Modeling approach. The results of the analysis indicate that interest or desire determines the behavior or business debt decisions of female entrepreneurs. The results of this study also show that female entrepreneurs' interest in business debt is determined only by entrepreneurial self-efficacy, while factors such as entrepreneur desirability, entrepreneur opportunity recognition, and entrepreneur social identity do not statistically influence their interest in business debt.